Cardiovascular safety of growth hormone treatment in Noonan syndrome: real-world evidence. Issue 1 (31st January 2022) - Romano, Alicia; Kaski, Juan Pablo; Dahlgren, Jovanna; Kelepouris, Nicky; Pietropoli, Alberto; Rohrer, Tilman R; Polak, Michel
Abstract : Objective: The study aims to assess the cardiovascular safety of growth hormone (GH) treatment in patients with Noonan syndrome (NS) in clinical practice. Design: The study design involves two observational, multicentre studies (NordiNet® IOS and the ANSWER Program) evaluating the long-term effectiveness and safety of GH in >38, 000 paediatric patients, of which 421 had NS. Methods: Serious adverse events, serious adverse reactions (SARs) and non-serious adverse reactions (NSARs) were reported by the treating physicians. Cardiovascular comorbidities at baseline and throughout the studies were also recorded. Results: The safety analysis set comprised 412 children with NS (29.1% females), with a mean (s.d. ) baseline age of 9.29 (3.88) years, treated with an average GH dose of 0.047 (0.014) mg/kg/day during childhood. Cardiovascular comorbidities at baseline were reported in 48 (11.7%), most commonly pulmonary valve stenosis (PVS) and atrial septal defects. Overall, 22 (5.3%) patients experienced 34 safety events. The most common were the NSARs: headache (eight events in seven patients) and arthralgia (five events in three patients). Two SARs occurred in one patient (brain neoplasm and metastases to spine). No cardiovascular safety events were recorded in patients with NS. Five cardiovascular comorbidities in five patients were reported after initiation of GH treatment: three cases of unspecified cardiovascular disease, one ruptured abdominal aortic aneurysm and one PVS. Conclusions: GH treatment had a favourable safety profile in patients with NS, including those with cardiovascular comorbidities. Prospective studies are warranted to systematically assess the safety of GH treatment in patients with NS and cardiovascular disease.